Age-related changes of micro-morphological subchondral bone properties in the healthy femoral head. Issue 11 (November 2020) - Ries, C.; Boese, C.K.; Stürznickel, J.; Koehne, T.; Hubert, J.; Pastor, M.-F.; Hahn, M.; Meier, S.L.; Beil, F.T.; Püschel, K.; Amling, M.; Rolvien, T.
Summary: Objective: Alterations in the subchondral bone (SCB) are likely to play a decisive role in the development of osteoarthritis (OA). Since aging represents a major risk factor for OA, the aim of the current study was to assess the microstructural changes of the subchondral bone in the femoral head during aging. Design: Femoral heads and matched iliac crest biopsies of 80 individuals (age 21–99 years) were collected post-mortem. The bone microstructure of the subchondral trabecular bone as well as the cartilage thickness (Cg.Th) and subchondral bone plate thickness (SCB.Th) were quantified using histomorphometry. The different subregions of the SCB were also imaged by quantitative backscattered electron imaging (qBEI) in 31 aged cases to assess the bone mineral density distribution (BMDD). Results: The detected linear decline of bone volume per tissue volume (BV/TV) in the femoral head with aging (Slope, 95% CI: −0.208 to −0.109 %/yr.) was primarily due to a decrease in trabecular thickness (Tb.Th, Slope, 95% CI: −0.774 to −0.343 μm/yr). While SCB.Th declined with aging (Slope, 95% CI: −1.941 to −0.034 μm/yr), no changes in Cg.Th were detected (Slope, 95% CI: −0.001 to 0.005 mm/yr). The matrix mineralization of the subchondral bone was lower compared to the trabecular bone and also decreased with aging. Conclusions: Regular changes of the SCB during aging primarily involve a reduction of Tb.Th, SCB.Th and matrix mineralization. Our findings facilitate future interpretations of early and late OA specimens to decipher the role of the SCB in OA pathogenesis.